Intelligent multidimensional data and image processing - De, Sourav; Bhattacharyya, Siddhartha 1975-; Dutta, Paramartha 1966- (Advances in multimedia and interactive technologies (AMIT) book series, 2018)
"This book brings a broad spectrum of artificial intelligence and its applications under the purview of 3D image processing so that it is able to trigger further inspiration among various research communities to contribute in their respective fields of applications thereby orienting these application fields towards 3D image processing and analysis"...